Political Rhetoric, Armed Violence and Threats to Democracy: An Analysis of Stochastic Terrorism Within the Media Ecosystem - Tatik Tatik; Rifqi Rifqi; Dinata Firmamansyah; Rosidin Rosidin; Sumarta Sumarta (Penerbit Hellow Pustaka, 2025)
This research is motivated by the rise of political violence fueled by the convergence of inflammatory political rhetoric and firearm accessibility. In the digital era, political communication has shifted from policy persuasion to an instrument of dehumanization that threatens the stability of deliberative democracy. This study aims to analyze how socio-psychological mechanisms and media ecosystems contribute to the phenomenon of contemporary political violence. The research method employed is a qualitative approach with library research. Secondary data were gathered from reputable scientific literature, policy reports, and relevant textbooks. Qualitative content analysis was conducted by integrating cognitive-neoassociation theory, totalism theory, and deliberative democracy theory to map the causality between mass communication patterns and the probability of violence. The results indicate that extreme political rhetoric creates a